Negotiating rites - Hüsken, Ute; Neubert, Frank (Oxford University Press, 2012)
Ritual has been long viewed as an indisputable part of tradition with the aim of creating harmony and enabling a tradition's survival. The authors in this collection argue, however, that this view can be seriously challenged and that ritual's embeddedness in negotiation processes is one of its central features.
Keywords: Aufsatzsammlung; Buddhismus; Hinduismus; Südasien; Ritual; Ritus; Verhandlung